Development of experimental chronic kidney disease and vascular calcification alters diurnal variation of phosphate and its hormonal regulators. Issue 21 (15th November 2020) - Svajger, Bruno A.; Riddoch, Justin L. H.; Pruss, Cynthia M.; Laverty, Kimberly J.; Ward, Emilie; Holden, Rachel M.; Adams, Michael A.
Abstract: The mineral‐bone axis is tightly regulated and dependent on renal function. In chronic kidney disease (CKD) progressive loss of renal capacity disrupts this axis over‐time, with marked changes in circulating calcium, phosphate, PTH, and fibroblast growth factor‐23 (FGF‐23). These changes contribute to the development of cardiovascular disease, like vascular calcification (VC), which worsens morbidity and mortality in CKD. Although the chronic changes in these circulating factors and their relationships are well known, no experimental studies have examined how the progressive development of CKD and VC alter the circadian rhythms of these factors. An adenine‐induced experimental model of CKD in rats was used to establish (i) general circulating trends, (ii) if renal dysfunction affects these observed trends, and (iii) identify potential changes in these trends caused by VC. This study clearly discerned patterns of daily variations in circulating minerals and hormones, finding that both phosphate and PTH follow modelable diurnal variations whereas calcium and FGF‐23 maintain relative stability over 24‐hr. Surprisingly, the development of CKD was not sufficient to disrupt these patterns of diurnal variation and only altered the magnitude of change; however, it was found that the diurnal rhythms of circulating phosphate and daily stability of calcium were only significantly altered in the setting of CKD with established VC. Abstract : In this article, we experimentally and progressively generated CKD in rats using an adenine‐based diet. We examined the effect of worsening CKD and the development of vascular calcification on the daily variations in circulating minerals (phosphate, calcium) and mineral‐regulating hormones (PTH, FGF‐23). It was found that CKD did not alter the daily patterns of circulating minerals and hormones, but the occurrence of VC in CKD did.